Role of Copper and Melatonin in the Pathogenesis and Therapy of Alzheimer’s disease - Nikas, Vaishnavi; Merat, Rutuja; Mukhmale, Vaishali; Sheikh, Aijaz; Khedekar, Swati; Biyani, K R (Asian Journal of Pharmaceutical Research and Development, 2025)
Alzheimer's disease (AD) is a neurodegenerative ailment that results in dementia and the death of neurones. It also causes cognitive impairment. Neurofibrillary tangles and amyloid-beta (Aβ) plaques are two of the pathological findings associated with this condition. A study that was conducted not too long ago revealed that Copper (Cu) dysregulation plays a significant role in the aetiology of Alzheimer's disease (AD) by producing oxidative stress and increasing the aggregation of Aβ. In the meanwhile, melatonin, a neurohormone that possesses powerful neuroprotective and antioxidant properties, has garnered interest due to the possibility that it might be used as a therapy for Alzheimer's disease (AD). Within the scope of this review, a comprehensive assessment of the most current research on the intricate connections that exist between Alzheimer's disease, melatonin, and copper homeostasis is presented. We investigate how an excessive amount of copper might exacerbate the pathogenesis of Alzheimer's disease (AD), as well as how the unique properties of melatonin can mitigate these effects. Through the chelation of excess copper and the reduction of oxidative stress, melatonin is a potential chemical that has a dual approach to addressing major aspects of Alzheimer's disease. A better understanding of the interaction between copper dysregulation and the protective mechanisms of melatonin may lead to the development of novel therapeutic approaches, which holds the potential to improve the treatment of Alzheimer's disease (AD).